Peningkatan Keterampilan Kegawatdaruratan Perawat di Rumah Sakit - Solehudin, Solehudin; Syabanasyah, Inas (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Medical emergencies, especially those related to trauma and cardiac arrest, require fast and precise handling by health workers, especially nurses in hospitals. This community service activity aims to improve the competence of nurses in handling emergency patients through Basic Trauma Cardiac Life Support (BTCLS) Training. This training includes theoretical explanations and direct practice related to cardiopulmonary resuscitation (CPR), airway management, trauma management, and emergency case simulations. The training methods used include interactive lectures, skill demonstrations, and clinical scenario-based simulations. Evaluations were conducted to measure the increase in participants' knowledge and skills before and after training. The evaluation results showed a significant increase in participants' understanding and skills in handling trauma and cardiac arrest cases. With this training, it is hoped that nurses can be more alert and professional in dealing with emergency conditions, thereby improving the quality of health services and patient safety. The continuation of this training program is recommended to ensure that nurses' competence is maintained and developed in accordance with developments in science and emergency service standards.